The perception of eye contact is associated with men’s need to belong, self-esteem, and loneliness - Manman Zhai; Heini Saarimäki; Jari K. Hietanen (PLoS ONE, 2025)
The present study (N =  367) investigated the association of the cone of direct gaze (CoDG; a range within which slightly averted gaze is accepted as direct gaze) width with the need to belong (NTB) and the possible further influence of NTB on self-esteem and loneliness. Results showed that: (i) men’s CoDG width predicted the NTB, self-esteem, and loneliness; (ii) men’s narrow CoDG predicted high loneliness via a high NTB and low self-esteem; (iii) a narrow CoDG was associated with low self-esteem via high loneliness only in high-NTB men. Among women, the CoDG width was not associated with the NTB, self-esteem, and loneliness. The findings are discussed considering the formation and maintenance of relationships together with gender differences.